The Inner Feelings and Emotions in Alan Walker's Selected Songs: "Faded," "Alone," and "Darkside" - Nora Wanti; Minsakutra Minsakutra; Al Amin (The Future of Education Journal, 2026)
This research analyzes the inner feelings and emotions reflected in Alan Walker’s selected songs entitled “Faded,” “Alone,” and “Darkside.” The study aims to identify the emotional expressions contained in the lyrics and explain how Alan Walker reflects his personal experiences and emotional conditions through his songs. This research applies a qualitative descriptive method using a biographical approach and expressive theory proposed by Abrams. The primary data consist of the lyrics from the selected songs, while supporting data are obtained from Alan Walker’s biography, interviews, and documentary videos discussing his musical career and personal experiences. The findings reveal that the songs contain dominant emotional themes such as sadness, loneliness, confusion, struggle, fear, anger, and hope. The lyrics represent emotional instability, feelings of alienation, and the search for identity, which are closely related to Alan Walker’s experiences as an international musician facing rapid success and social pressure at a young age. Through symbolic language, metaphors, repetition, and emotional expressions, Alan Walker communicates his psychological experiences and emotional struggles to listeners. This research concludes that song lyrics function not only as entertainment but also as a medium for emotional expression, self-reflection, and artistic communication. Furthermore, this study contributes to literary studies by demonstrating that popular music lyrics can be analyzed as literary works that reflect personal experiences, emotional conditions, and human psychological realities.